Heart rate and blood lactate responses during training and competition in elite badminton players - Smith, J. A.; Chang, C. C. (Medicine & Science in Sports & Exercise, 1999)
Male badminton players (N = 13) were physiologically evaluated during an intense interval training session and at another time during a 3-set game. There were no significant correlations between heart rate and lactate. Heart rates and lactate levels were significantly higher at training than in a game. Lactate increased progressively during the training session but remained relatively stable during the game. Implication. The physiological demands of training are higher than in a game. In badminton, heart rate should not be used to infer lactate or workload levels.